Arquivos bordados: arte como costura da ancestralidade feminina japonesa - Sampei, Gabriela Yumi [UNESP] (2019)
The aim of this research is mainly to recognize the influences of Japanese ancestry in own artistic production, based on the study of the artisanal textile present in the artist 's particular family context, and based on the investigation of Japanese memory, archival and ancestral concepts from the perspective of Roland Barthes (2015), Gaston Bachelard (1996), José Yamashiro(1993), PhD thesis of Prof. Dr Joedy Luciana Barros Marins Bamonte(2004), and the master thesis of Laís Miwa Higa(2015). Since it is a research in Visual Arts according to the methodological instance, photography and the embroidery are present in the elaboration of the artistic works to obtain a relation between the studies of the concepts and the chosen techniques. The artistic production focus on photography of family portrait with intervention of the embroidered line, in order to interweave memory, archive and ancestrality in an environment of Okinawan immigration and recognition of the familiar production in the handmade textile